A code-compliance assessment tool for fire prevention measures in educational facilities. Issue 3 (1st July 2021) - Salaheldin, Mohammad H.; Hassanain, Mohammad A.; Hamida, Mohammad B.; Ibrahim, Ahmed M.
Abstract : Purpose: This research presents the applicable international fire code requirements for educational facilities, in a comprehensive manner, and the findings of a case study to assess the level of compliance with these requirements. Design/methodology/approach: A review of literature, fire codes and standards was conducted to identify the various sources of fire hazards in educational facilities and the required prevention measures. Accordingly, a code-compliance worksheet for assessing the fire prevention measures was developed. The worksheet included 34 prevention measures. It was implemented in a pharmacy college building, as a case study, to assess the compliance level with the code requirements. Recommendations were developed to improve the level of fire prevention in the case study facility. Findings: The implemented worksheet facilitated identifying all the shortcomings in the prevention measures, in a methodological manner. These shortcomings included exceeded travel distance, absence of assembly point, inactive record keeping of fire inspection and maintenance works, deterioration of some extension cords and switches, alteration of some emergency doors, storage of combustibles in some electrical rooms and obstructions of the fire apparatus access road. Practical implications: The research provides an assessment tool for fire prevention in educational facilities, which can be used by professionals for a code-compliant inspection. The findings of the case study as an example serve to expand the inspectors' observational significance while reducing subjectivity. Originality/value: This research contributes to the educational facilities' context of health and safety domain in the literature. The research classifies the required fire prevention measures for an educational facility, according to the international applicable codes and standards. The case study demonstrates an applicable methodology for assessing the fire prevention measures and requirements.